Autohydrolysis pretreatment combined with refining for improved enzymatic hydrolysis of multiple feedstock - Han, Qiang; Ertaş, Murat; Jameel, Hasan; Chang, Hou-min; Phillips, Richard (Amer Chemical Soc, 2014)
[No Abstract Available]
247th National Spring Meeting of the American-Chemical-Society (ACS) -- MAR 16-20, 2014 -- Dallas, TX
Keywords: [No Keywords]